Sosialisasi dan Pendampingan Penyusunan Laporan Keuangan Berbasis SAK EMKM di UMKM Negeri Makariki - Jusuf Leiwakabessy; A. Buiswarin; J. Ngilyaubun; D. Nabila; A. Timisela; G Laisatamu; Audrey Leiwakabessy (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2026)
Micro, Small, and Medium Enterprises (MSMEs) and Village-Owned Enterprises (BUMNeg) in Makariki possess regional economic potential. However, business managers face cash flow recording obstacles. They have not implemented standard bookkeeping. This community service aims to provide training and mentoring in financial document preparation using the Financial Accounting Standards for Micro, Small, and Medium Entities framework. The implementation method consists of preparation, execution, and evaluation stages. The execution stage includes initial testing, material presentation, interactive discussion, and final testing. Evaluation results indicate this program resolves participants' financial literacy problems. Participants' understanding regarding bookkeeping accounts and calculating profit and loss increased. Participants can compile drafts of income statements, financial positions, and supporting notes independently. In conclusion, intensive mentoring changes participants' mindsets from conventional management to a more structured one. Systematic bookkeeping helps participants separate personal and business assets. These records also serve as administrative requirements to access additional capital from banks or government assistance programs. This program supports the transparency and accountability of village fund management through BUMNeg.